2021
DOI: 10.1093/advances/nmaa096
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Total Red Meat Intake on Glycemic Control and Inflammatory Biomarkers: A Meta-Analysis of Randomized Controlled Trials

Abstract: Our objective was to conduct a systematic review and meta-analysis to assess the effects of total red meat (TRM) intake on glycemic control and inflammatory biomarkers using randomized controlled trials of individuals free from cardiometabolic disease. We hypothesized that higher TRM intake would negatively influence glycemic control and inflammation based on positive correlations between TRM and diabetes. We found 24 eligible articles (median duration, 8 weeks) from 1172 articles searched in PubMed, Cochrane,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 53 publications
3
18
0
Order By: Relevance
“… 38–40 Conversely, the results of other random intervention trials have shown inconsistent evidence. 41 However, recent studies have found that replacing red meat with other nonmeat protein foods can reduce the risk of T2DM, 42 , 43 which subsequently demonstrates the role of red meat in T2DM. In the present study, we found that the median refined grain intake was the same between the two groups, but the average refined grain intake of T2DM patients was 346.27 g, which was higher than that of participants without diabetes (318.66 g).…”
Section: Discussionmentioning
confidence: 99%
“… 38–40 Conversely, the results of other random intervention trials have shown inconsistent evidence. 41 However, recent studies have found that replacing red meat with other nonmeat protein foods can reduce the risk of T2DM, 42 , 43 which subsequently demonstrates the role of red meat in T2DM. In the present study, we found that the median refined grain intake was the same between the two groups, but the average refined grain intake of T2DM patients was 346.27 g, which was higher than that of participants without diabetes (318.66 g).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, most prospective cohort studies [8e11,43] used hard disease endpoints (i.e. risk of disease) over 5 years or longer, whereas the present study and RCTs [33,34] used intermediate disease markers (e.g. fasting insulin, HOMA-IR, triacylglycerols, and HDLcholesterol) over a shorter period.…”
Section: Discussionmentioning
confidence: 93%
“…In the present study, our findings do not support that adults after rapid weight loss should reduce or avoid unprocessed red meat intake. Similarly, in two meta-analyses of randomised controlled trials (RCTs), O'Connor et al [33,34] found that intake of red meat did not result in deterioration of glycaemic and cardiometabolic risk factors, although the RCTs included did not have a large weight loss phase. In addition, although low red meat intake is recommended by DASH dietary patterns, some RCTs showed that DASH diets had equivalent efficacy in decreasing cardiometabolic risk factors when they contained higher amounts of red meat [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Food groups rich in vegetable fats, such as olive oil [ 26 ] and nuts [ 26 ], as well as other plant-foods such as soy [ 27 ], legumes, and pulses [ 28 ], have been shown to cause a non-significant decrease in CRP levels. Among animal foods, dairy products [ 29 ] have shown a significant reduction effect on CRP levels, while others, such as red meat [ 30 ] and eggs [ 31 ], have been shown to produce null results.…”
Section: Major Food Groups Dietary Patterns and Inflammationmentioning
confidence: 99%